Controllable preparation of graphitic carbon nitride nanosheets via confined interlayer nanospace of layered clays - Jiang, G.; Zhou, C.; Xia, X.; Yang, F.; Tong, D.; Yu, W.; Liu, Shaomin (Elsevier Science, 2010)
This work described the size-controllable preparation of novel graphitic carbon nitride nanosheets using the interlayer space of smectite clays as a confined nanoreactor through cyanamide condensation. The prepared solids were characterized by X-ray diffraction, FT-IR, SEM and TEM. Results revealed that when ammonium-saponite was used, graphitic carbon nitride with an average crystal size of about 4.8 nm, the particle size of 50–100 nm and a C/N = 1.931 was obtained. When montmorillonite was used, graphitic carbon nitride with a crystal size of approximate 6.0 nm, the particle size of 100–150 nm and a C/N = 0.959 was yielded. The space-confined preparation of carbon nitride using layered clay minerals not only changes the texture of the resultant carbon nitride, but also alters the composition of products owing to the change of the whole reaction scheme to yield some new species. Such controllability over the size can be ascribed to the difference of the interlayer space and the cation exchange capacity of saponite and montmorillonite.